An Integrated Type and Dimensional Synthesis Method to Design One Degree-of-Freedom Planar Linkages With Only Revolute Joints for Exoskeletons - Shen, Z.; Allison, Garry; Cui, Lei (ASME Press, 2018)
Copyright © 2018 by ASME. Exoskeletons can assist wearers to relearn natural movements when attached to the human body. However, most current devices are bulky and heavy, which limit their application. In this paper, we integrated type and dimensional synthesis to design one degree-of-freedom (DOF) linkages consisting of only revolute joints with multiple output joints for compact exoskeletons. Type synthesis starts from a four-bar linkage where the output link generates the first angular output. Then, an RRR dyad is connected to the four-bar linkage for the second angular output while ensuring that the overall DOF of the new mechanism is 1. A third output joint is added in a similar manner. During each step, dimensional synthesis is formulated as a constrained optimization problem and solved via genetic algorithms. In the first case study, we developed a finger exoskeleton based on a 10-bar-13-joint linkage for a natural curling motion. The second case study presents a leg exoskeleton based on an 8-bar-10-joint linkage to reproduce a natural walking gait at the hip and knee joints. We manufactured the exoskeletons to validate the proposed approach.